RUT HOUSE WEBBER, Formulistic diction in the Spanish ballad. University of California Press. Berkeley and Los Angeles. 1951 . (University 01 California Publications in Modern Philology, vol . XXXIV. núm. 2. págs . 175-278) . - Varillas Montenegro, Alberto (1953)
No contiene resumen